Assistance from Posyandu Cadres to Overcome Digestive Problems of Babies & Toddlers in Preventing Stunting in Harjosari Village, Sukajadi District, Pekanbaru, Riau: Pendampingan Kader Posyandu Mengatasi Masalah Pencernaan Bayi & Balita dalam Pencegahan Stunting di Kelurahan Harjosari, Kecamatan Sukajadi, Pekanbaru, Riau - Rizka Mulani; Annisa Fathin; Selvi Arianti; Revalina Sutarmadi; Forwaty, Erni (Universitas Lancang Kuning, 2024)
One of the factors causing stunting is infectious diseases. An infection that is often suffered by babies under five is diarrhea. Parents need to know the role of diarrhea in causing stunting. The role of Posyandu Toddler cadres is very important in providing knowledge to parents. Through the Student Creativity Program (PKM), the team carries out community service activities in the form of mentoring cadres using the brainstorming method. The activity aims to increase cadres' knowledge about digestive problems in babies and toddlers in the context of preventing stunting. Community service activities are carried out at the Toddler Posyandu, Harjosari Village, Pekanbaru, Riau, namely at six Posyandu. The media used are videos, material presentations and leaflets. There are 3 stages of activity, namely preparation, brainstorming and evaluation. The results obtained showed an increase in the level of high knowledge of 53% between the pre-test and post-test results. Mentoring cadres through the brainstorming method can increase cadres' level of knowledge. It is hoped that brainstorming activities can continue to be carried out between cadres, the community and Puskesmas officers so that health problems can be immediately addressed and prevented.